Controller Responsibility of the Insurance Company in the Event of Failure to Pay the Insurance Policy of PT Jiwasraya Insurance Company - Soca Daru Indraswari (East Asian Journal of Multidisciplinary Research, 2023)
Law has the goal of producing orderly social rules, producing discipline, balance and justice. Mochtar Kusumaatdmaja said "By achieving order in society, it is hoped that human interests will be protected". According to Sudikno Mertokusumo, the rule of law, in addition to protecting human interests against the dangers that threaten them, also regulates the relationship between humans. By regulating relations between human beings, in addition to creating order or stability, it is hoped that conflicts or disturbances of these interests can be prevented or resolved. Satjipto Rahardjo explained more clearly, according to him, the presence of law among others functions to integrate and coordinate interests that can conflict between one interest and another